Speaking Skills Improvement With Sociodrama Method in Subjects Indonesian Class V SDN Angarang 04 - Eri Hoeriyah; Febri Isnawati; M. Ilham Rahman Riyadi (International Journal of Science and Applied Science: Conference Series, 2020)
The purpose of this classroom action research was to improve students' speaking skills through the application of the sociodrama method to fifth-grade students at SDN Sindangbarang 04. This study used classroom action. The subjects of this study were fifth-grade students at SDN Sindangbarang 04, totaling 27 students (14 boys and 13 girls). The objects of this research are speaking skills and the sociodrama method. This classroom action research was conducted through two cycles. From the results of the actions from cycle I to cycle II, there was an increase in students' speaking skills. Researchers used a research design developed by Kemmis and Taggart with a spiral model whose implementation consisted of four series of activities as a cycle, namely planning, implementing, observing, and reflecting. Data collection techniques in this study are qualitative data and quantitative data.The results showed that learning speaking skills using the sociodrama method could improve the speaking skills of fifth-grade students at SDN Sindangbarang 04. The improvement in speaking skills using the sociodrama method was as follows, (1) the average value of speaking skills in cycle I was 69.03, an increase of 13.53 from the pre-action value of 55.5, and the percentage of completeness increased by 18.5% from the pre-action percentage of 22.2% to 40.7% (2) the average value of speaking skills cycle II 78 increased 8.97 from the pre-action value of 69 .03, and the percentage of completeness increased by 48.18% from the pre-action percentage of 40.7% to 88.88%.